A paired comparison of thawed and liquid plasma. Issue 4 (23rd November 2016) - Backholer, Lucy; Green, Laura; Huish, Sian; Platton, Sean; Wiltshire, Michael; Doughty, Heidi; Curnow, Elinor; Cardigan, Rebecca
Abstract : BACKGROUND: To make plasma readily available to treat major hemorrhage, some centers are internationally using either thawed plasma (TP) or "never‐frozen" liquid plasma (LP). Despite the routine use of both, there are limited data comparing the two. The hemostatic properties of LP were evaluated and compared to TP in a paired study. STUDY DESIGN AND METHODS: Two ABO‐matched plasma units were pooled and split to produce 1 unit for LP and 1 unit for TP. Samples of TP and LP, stored at 2 to 6°C, were tested for a range of coagulation factors, thrombin generation, and rotational thromboelastometry. An additional 119 units of LP were collected and analyzed for markers of contact activation (S‐2302 cleavage) and cellular content. RESULTS: LP and TP were compared, up to 7 days of storage, with results showing no difference in the rate of change over time for any variable measured. When compared to Day 5, LP on Day 7 showed no difference for any factors measured; however, on Day 11 Factor (F)II, FV, FVII, and protein S (activity) were lower. Analysis of 119 LP units showed that 26 of 119 (22%) exhibited cold‐induced contact activation by Day 28. CONCLUSION: LP and TP were comparable in terms of hemostatic variables up to 7 days of storage. Decreasing coagulation factor activity along with an increased activation risk during storage of LP needs to be balanced against availability to supply and clinical need when considering using LP with more than 7 days of storage.